The Cercle de l’Ermitage by Alberto Sartoris. Axonometry as a Synthetic Representation of the Project (diségno, 2022)
A chromolithograph by Alberto Sartoris, published in 1936 in The Architectural Review [Morton Shand 1936], depicts an axonometric cutaway of the dance floor and bar of the Cercle de l’Ermitage, designed and realised by the architect in 1935, transforming an old mill into a cultural and social centre for international exhibitions, a private club for artists [1]. Sartoris articulated the interior with a succession of superimposed platforms “in a radically modern way, in order to embody and conceptualize the space into a manifesto of rationalistic architecture, without modifying the outer envelope” [Dunant 2016, p. 78], as requested by the Swiss authorities [2]. [read more]